"Just a Gigolo": Differences in Advertisements of Male-for-Female and Male-for-Male Online Escorts. Issue 1 (2nd January 2018) - Pruitt, Matthew V.
ABSTRACT: Our knowledge of men who offer sexual services exclusively to women via the Internet and how they differ from male-for-male escorts is quite limited. Escort advertisements are likely to reflect differences in both the providers themselves and the targets of these ads. A content analysis of online ads posted by male-for-female and male-for-male escorts is conducted in order to compare these groups of sex workers with regard to demographics, personal descriptors, fees charged, sexual and nonsexual services provided, disease status, involvement in pornography, and pictures posted (face shots, penis and butt pics, wearing of suggestive attire, sexual poses).